Aktivitas Fisik dan Pola Makan Berhubungan dengan Kejadian Diabetes Melitus di RSUD Margono - Lasya Al Imani Fielsa Wastam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Diabetes Mellitus is a systemic disease with increasing prevalence every year in the 21st century. DM currently occurs not only in the elderly group, but young people are also starting to get DM. Slow and slow handling can trigger serious complications such as cardiovascular, renal, and neuropathy disorders. Analyzing the relationship between physical activity and diet with DM at Margono Hospital. This study is a cross-sectional study with patients at Margono Hospital as the research population. The inclusion criteria for respondents are understanding Indonesian, being able to communicate verbally, and being willing to participate. On the other hand, the exclusion criteria include people with dementia, deafness, blindness, and decreased consciousness. The total sampling technique obtained 53 respondents. The instrument was a questionnaire for diet and GPAQ for physical activity. Data analysis with Chi Square. The majority of respondents were over 55 years old (50.9%), female (60.4%), low physical activity (56.6%), poor diet (60.4%), and had DM (60.4%). Bivariate analysis showed that physical activity and diet had a relationship with the incidence of DM with p-values ​​of 0.002 and 0.000, respectively. Physical activity and diet had a significant correlation with the incidence of DM at Margono Regional Hospital. Health promotion efforts are needed by establishing cooperation between sectors facilitated by the health office, especially by empowering cadres and community leaders in related areas to reduce the incidence of DM and maintain the quality of life of people with DM.